Інтертекстуальність як риса поетики жанру фентезі (на прикладі романів Террі Претчетта) - Канчура, Є. (Питання літературознавства, 2009)
Розглядається моделювання Террі Претчеттом мультикультурного суспільства у тектуалізованому просторі Дискосвіту, вплив інтертекстуальності на виникнення стереотипів сприйняття „чужого народу” та пошук засобів ведення діалогу між культурами. The key word in studying of fantasy and science fiction is „premise”, an assumption which forms the plot. Fantasy-premise is intertextual, based on knowledge about the world which comes from unconscious experience and cultural background of the epoch. Terry Pratchett, English fantasy writer, creates the world where text has real power: all the citizens of the Multiverse live in the „library-space” where the interaction of the stories creates the reality. The article focuses on Terry Pratchett’s model of multicultural society in textualized reality of Discworld, the influence of intertextuality on the stereotypes of the „other” people and attempts of starting dialogues between the cultures.